In Vivo Recovery and Survival of Monoclonal-Antibody-Purified Factor VIII Concentrates - Kasper, Carol K; Kim, Hugh C; Gomperts, Edward D; Smith, Kenneth J; Salzman, Phyllis M; Tipping, Diane; Miller, Robert; Montgomery, Robert M (Thrombosis and Haemostasis, 1991)
In response to reports of discrepant in vitro assays of high-purity concentrates, a double-blind crossover study of in vivo recovery and half-life of two brands of monoclonal-antibody-purified factor VIII concentrates (Monoclate and Hemofil-M) was performed in 23 patients with hemophilia A. In vivo recoveries were close to values predicted from the labelled unitage when plasma samples were assayed by a one-stage method. When a two-stage assay was used, lower recoveries were calculated and the recovery with Hemofil-M was slightly but significantly lower than that with Monoclate. The concentrates were re-assayed in vitro by the two-stage method. Monoclate (which is assayed by the manufacturer using a two-stage method) contained 97% of the labelled potency and Hemofil-M (which is assayed by the manufacturer using a one-stage method) contained 81% of the labelled potency. Differences in in vitro and in vivo assay methods contribute to disparities between expected and observed factor VIII recovery. Clearance of Hemofil-M was significantly faster than that of Monoclate, but volume of distribution at the steady state, mean residence time, and plasma half-disappearance times of the two concentrates were not significantly different.